Organic material mulching regulated core microbial groups to promote soil carbon and nitrogen cycling and improve faba bean productivity under a triple-cropping system in purple soil hilly region of southwest China - Ren, Ke; Song, Wenfeng; Wei, Zehui; Song, Lixia; Liu, Ming; Zhou, Yuling; Zhen, Yuzhuo; Wu, Xinyao; Gu, Kaiyuan; Simarani, Khanom; Wang, Longchang (Frontiers in Microbiology, 2025)
BackgroundIntensive agricultural production leads to the reduction of soil carbon (C) and nitrogen (N) reserves, and organic material mulching (OMM) can improve microbial community structure and promote C and N accumulation. The multi-cropping system based on legumes can provide abundant organic mulching material and improve soil quality, but the mechanism by which OMM provides ecological benefits via C and N cycling in this system is still unclear.MethodsIn this study, a field experiment of organic mulch under the triple-cropping system of faba bean (Vicia faba L.)-corn (Zea mays L.)-sweet potato (Ipomoea batatas Lam.) was performed. Four treatments were set up: without organic material mulching (CK), straw mulching (S), milk vetch (Astragalus sinicus L.) mulching (M), and straw and milk vetch mulching (SM). The dynamic changes in soil aggregates, C and N contents, enzyme activities, microbial communities and faba bean productivity under organic mulching were studied for 2 years (from October 2020 to May 2022).ResultsThe results demonstrated that supplementation of OMM (S, M, and SM) significantly improved the stability of soil aggregates, the nutrient (C and N) contents, and the activities of acquiring enzymes compared to CK. OMM promoted the establishment of key microbial communities dominated by Actinobacteria, Bacteroidetes, Ascomycota, and Basidiomycota. Predicted functional profiles based on PICRUSt and FUNGuild analyses suggest possible upregulation of up-regulated genetic information processing, metabolism, and organismal systems functional pathways. Additionally, the enhancement of soil C and N cycling efficiency may be associated with an increase in the proportion of saprotrophs and symbiotrophs. Both the random forest model (RFM) and partial least squares path model (PLS-PM) demonstrated that OMM increased faba bean productivity by improving soil microbial diversity and the efficiency of C cycling.ConclusionThis study highlighted that OMM could promote C and N cycling by regulating core microbial groups, thereby improving the faba bean productivity in dryland of purple soil hilly region of southwest China.